Pengujian dan Analisis Keamanan Website Menggunakan Acunetix Vulnerability Scanner - Afif Zirwan (SEULANGA SYSTEM PUBLISHER, 2022)
The Covid-19 pandemic indirectly accelerated the 4.0 Industrial Revolution where technology became an important point in the industrial movement. Changes that are forced quickly, sometimes release some application developers to test the product to be implemented, because it is required quickly to compensate for the change. Padang Institute of Technology (ITP) also made rapid changes to its official website, to provide actual information of campus activities during this pandemic. Conduct testing and analysis of the extent of itp website security and provide troubleshooting advice from the results of the analysis. Testing is done using the Acunetix Vulnerability Scanner tool against the ITP website. The method used is descriptive analysis, which is the data obtained presented in the form of sentences described, thus providing clarity from the results of the analysis carried out.The results obtained from this study are ITP websites with acunex threat at level 3 which includes High theory and scanning time used for 2 Hours 5 minutes. In this study there were 714 alerts or gaps found consisting of 94 at high level, 25 at medium level, 46 at low level and 549 at informational level. Here is an explanation of the alert or loopholes found in the scanning website. From the analysis data it was concluded that in testing using acunetix itp website is at level 3, after improvement of itp website is at level 1.